A Review On Control Strategy For Electro-Mechanical Rubber Belt Continuously Variable Transmissions (CVT) - Ariyono, S.; Cholis, N. (2010)

(untitled)
Because of its significant advantages over other transmissions, including its simple construction, smooth operation, easy drivability, low cost, easy maintenance, the rubber V-belt continuously variable transmission (CVT) has been widely used in low-power vehicles such as snowmobiles and motorcycles. The works on control strategy for electro-mechanical have been published including in journal, conference as well workshop proceedings, standard, books and others. The current paper reviews the basic concepts of operating system CVTs, system of electro-mechanical rubber belt CVT, and related works. Challenges for future research on modeling and control strategy for electro-mechanical CVT are also discussed.